Organization of the educational process in a modern higher education institution based on a facilitative approach - Vorobieva, Eugene; Chebakova, Yu. G. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The article elucidates the peculiarities of reforming the educational process in institutions of higher education and defines the relevance of the activities of the modern teacher of institution of higher education institution as a facilitator; analyzes and summarizes the features of the implementation facilitative approach in the educational space of the modern HEI; the publication contains generalizations and conclusions about the content and peculiarities of implementation facilitating approach in the professional activities of scientific and pedagogical workers of HEI.

В статті висвітлено особливості реформування освітнього процесу у закладах вищої освіти; визначено актуальність діяльності сучасного викладача закладу вищої освіти як фасилітатора; проаналізовано та узагальнено особливості впровадження фасилітативного підходу в освітній простір сучасних ЗВО; публікація містить узагальнення та висновки щодо змісту та особливостей впровадження фасилітативного підходу в професійній діяльності науково-педагогічних працівників ЗВО.
Организація освітнього процесу в сучасному закладі вищої освіти на засадах фасилітативного підходу
Keywords: educational process; modern higher education institution; facilitative approach; освітні процеси; фасилітативні підходи; заклади вищої освіти